Critical Feminist Approaches to Migration and Mobility Justice in Canada: Guest Editors' Introduction - Kouri-Towe, Natalie; Mahrouse, Gada (ACME, 2023)
This themed section examines how inequality constrain and enable contemporary human movement at state border crossings. It responds directly to questions, practices, and knowledge gaps that arise from critical migration/refugee studies, critical tourism studies, border studies, and/or mobility justice research by denaturalizing assumptions about the rights of some to choose to move across borders freely and others who are forced to leave, denied access, or detained. In so doing, we highlight research on human mobilities and borders in Canada to advance understandings on the dynamics of territorial control and access to state borders. What links the articles is the commitment to examining the reproduction of power through the following three shared understandings and starting points: (1) a critique of the Canadian nation state’s global reputation as exceptionally humanitarian (Nguyen and Phu 2021); (2) a consideration of the global entanglements of racial capitalism and colonialism that structures human movement (Gutiérrez Rodríguez 2018); and (3) an understanding that the mobilities of some and the immobilities of others coexist and are in fact co-produced (Ahmed et al. 2020; Bauman 1998; Sheller 2018).